Transition in determinants of maternal malnutrition in India over a period of two decades - Sengar, Vijayata; Kaur, Gurkiran (International Journal Of Community Medicine And Public Health, 2023)
Background: In-depth understanding of the transition in the determinants, will aid in comprehending the potential changes in the future, reducing adverse outcomes and supporting ongoing nutrition and health programmes. Most of the studies have studied the determinants at a particular point in time, making it crucial to understand how these determinants have transitioned with the passing years. The present study was conducted to assess the transition in determinants of maternal malnutrition in India over a period of two decades by secondary data analysis using data from national family and health surveys. Methods: For the present exploratory study, secondary data for India was obtained from the DHS program. Data analysis was carried out using SPSS version 20 and above. Thinness [body mass index (BMI) <18.5 kg/m²] was used as the dependent variable. Binary logistic regression analysis was used to ascertain the effects of selected characteristics on the dependent variable and to identify transition in determinants over two decades by comparing the datasets. Results: Determinants of thinness like the place of residence, parity and partner’s occupation remained the same for the first decade however, changed in the last decade to socioeconomic status (OR 4.6: 95% CI [4.2-5.1]), age (OR 4.4: 95% CI [3.7-5.2]) and anemia levels (OR 2.3: 95% CI [2.0-2.7]). Conclusions: The trend clearly indicates that the focus of government programs and policies needs to change and implies that a holistic approach is necessary for improvement.